GLOF mitigation strategies - lessons learned from studying the Thulagi Glacier Lake, Nepal - Hanisch, J.; Pokhrel, A. P.; Grabs, W. E.; Dixit, A. M.; Reynolds, J. M. (Journal of Nepal Geological Society, 2000)
The results of an interdisciplinary study of the Thulagi Glacier Lake in Manaslu Himal in 1996 were in part surprising: different from remote sensing and geomorphologic interpretations, the Thulagi Lake is not dammed by a terminal moraine. Instead, the natural dam is composed of a huge, apparently old, thick, and slowly melting dead-ice body covered by mainly lacustrine sediments. Therefore, the most common mechanism of GLOF generation, the breaching of the damming terminal moraine by overtopping surge waves, can be ruled out in this case. Another important result of the field studies at the Thulagi Lake was the finding that most of the sediments of the dam area are lacustrine silts and fine sands with erratic boulders in-between. That implies that these sediments (hitherto believed to be of glacier origin) were deposited in a former lake. This case study demonstrates two fundamental facts: (i) each individual glacier lake has got its own development mechanism without the knowledge of which reliable statements on the lake's stability and its potential outburst hazard cannot be made, (ii) the hazard assessments of a glacier lake can only be done successfully in a multidisciplinary approach and by extensive field work. Remote sensing techniques still do have their limitations in this domain. Mitigation strategies have to focus on both: the GLOF hazard as well as the vulnerability of the area in the downstream. Only a combination of these two factors (by using the formula: disaster risk = hazard x vulnerability) can lea d to results that can convince the decision-makers on the need and effectiveness of mitigation work.